Hypertriglyceridemia induced pancreatitis management – a case report - Mufti, Aisha Kulsoom; Ullah, Naqeeb; Hayat, Muhammad; Aimal Khan, Muhammad (Journal of the Pakistan Medical Association, 2023)
Acute pancreatitis results in high morbidity and mortality. Gallstones and alcoholism are considered leading causes of acute pancreatitis. However, increasing prevalence of obesity, diabetes and lifestyle choices has resulted in Hypertriglyceridemia induced pancreatitis (HTAP) becoming more common. HTAP is said to be more severe than other causes. The treatment options available vary including intravenous (IV) insulin, heparin, plasma exchange, fibrates, niacin, omega three fatty acids and dietary restrictions. This is a case report of a patient presenting with HTAP and the dilemma treating physicians faced in trying to balance the need for urgent treatment with invasiveness of procedure and paucity of evidence. Keywords: Hypertriglyceridemia induced Acute pancreatitis (HTAP), Lipoprotein lipase (LPL), Triglycerides (TG). Deep vein thrombosis (DVT), Systemic inflammatory response syndrome (SIRS), Hypertriglyceridemia (HTG), Infusions, Intravenous (IV).